2022
DOI: 10.1002/admi.202200738
|View full text |Cite
|
Sign up to set email alerts
|

GQDs Incorporated CoPc Nanorods for Electrochemical Detection of Dopamine and Uric Acid

Abstract: Dopamine (DA) and uric acid (UA) are biomolecules of great consideration that coexist in human body. It is essential and challenging to detect them simultaneously with high sensitivity. This paper reports a novel electrochemical biosensor based on the nanocomposites of cobalt phthalocyanine (CoPc) anchored with graphene quantum dots (GQDs) for DA and UA detection. The GQDs incorporation on CoPc nanorods with partial end stretching significantly enhances the electrocatalytic activity and promotes the electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For example, DA exists as an essential neurotransmitter in the central nervous system, which is associated with behavioural reactions and brain functions, and normally it exists in the range of 0.387–1.548 μM in urine and lower than 130 pM in human whole blood. 4,5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DA exists as an essential neurotransmitter in the central nervous system, which is associated with behavioural reactions and brain functions, and normally it exists in the range of 0.387–1.548 μM in urine and lower than 130 pM in human whole blood. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…For example, DA exists as an essential neurotransmitter in the central nervous system, which is associated with behavioural reactions and brain functions, and normally it exists in the range of 0.387-1.548 μM in urine and lower than 130 pM in human whole blood. 4,5 Although many studies have been reported to solve the interference problem, biofouling and chemical fouling of the electrode are regarded as two crucial issues that restrict the practical applications in real sample analysis. 6 Biofouling is caused by the nonspecific adsorption of biomacromolecules (especially proteins) on the electrode surface when used in complex biological fluids (such as blood, saliva, urine, and serum), which could impede the transport of analytes and greatly affect the sensitivity, accuracy, and stability of electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…205 Another study used GR quantum dots (GQDs) coupled with cobalt phthalocyanine (CoPc) to modify glassy carbon electrodes (GCEs). 198 The resulting CoPc/GQDs/GCEs showed superior electrocatalytic activity for the simultaneous detection of dopamine (DA) and uric acid (UA) in PBS, outperforming traditional CoPc electrodes. The CoPc/GQDs/GCE showed reversible DA redox peaks and an irreversible UA oxidation peak on CV curves displaying heightened sensitivity and selectivity for simultaneous DA and UA detection.…”
Section: Voltammetry Techniquesmentioning
confidence: 99%